The Role of Service Quality Influence on Students’ Satisfaction in Tanzanian Higher Learning Institutions: A Preliminary Investigation - Victor William Bwachele; Yee-Lee Chong; Gengeswari Krishnapillai (Universitas Internasional Batam, 2023)
From a student’s perspective, the essential functions of a higher learning institution (HLI) include providing students with the teaching and learning infrastructures lodgings, assigning experts to sharpen students' theoretical and applied knowledge and critical thinking skills, and offering social, cultural, and athletic activities. However, as public financial support is shared among many HLIs in Tanzania, the HLI needs to increase its monetary fund through tuition collection. Quality services that meet the student’s expectations increase the student’s satisfaction which in turn encourages the enrollment of future students through the spread of positive word of mouth about the HLI. In analysing how the HLIs students have defined service quality dimensions and satisfaction, the researcher collected qualitative data from 15 final-year students from science, social science, and business disciplines. They were analysed using content analysis. The result shows that researchers can use additional items to measure specific service quality dimensions: perceived transparency and trust in an institution on top of the conventional (service quality, (SERVQUAL)) items measured by past researchers. In addition, the researcher identifies two additional service quality dimensions: perceived transparency and trust in an institution. This article explains how researchers can use service quality dimensions pertinent to the study environment to find more systematic to enhance the literature on service quality.